Strategic management of e-commerce in the consumers of Sky Peru SAC - Seminario Unzueta, Randall Jesús (2022)
Objectives: determine the strategic management of electronic commerce in the consumers of the company Sky Perú S.A.C. Materials and methods: this research has a quantitative approach of an applied type, and its methodological design is a non-experimental cross-sectional research, the level of research is descriptive; counting on a sample made up of 200 consumers of the company Sky Peru SAC who make purchases through web pages, the technique used during data collection was the survey and the instrument was the questionnaire with 21 items and 6 dimensions, the data was analyzed using SPSS 26 software. Results: indicate that the strategic management of electronic commerce was determined by a low level with 60.5%, followed by a high level of 18%, a very low level with 14.5% and a very high level with 7. %; in relation to the dimensions purchase of goods or services (66%), means of payment (66%), computer web pages (69%) and use of computer network (37%). Conclusions: regarding the strategic management of electronic commerce in consumers, controlled mechanisms of electronic purchase and sale must be implemented that allow the consumer to trust and make purchases in the most used virtual media.